PENGARUH PENGGUNAAN SERAT KULIT ROTAN SEBAGAI PENGUAT PADA KOMPOSIT POLIMER DENGAN MATRIKS POLYESTER YUKALAC 157 TERHADAP KEKUATAN TARIK DAN DAN TEKUK - Sarjito Jokosisworo (TEKNIK, 2009)
This time, rattan bark fiber’s used in furniture industries and home industries because it is easy to get, cheap,not to be danger for our health, and it can lesson environment pollution (biodegradability); so, with exploit ascomposites lasing fibre, later, it can overcome the environment problem. The rattan bark development ascomposite material has already know, in view of the raw material of natural fibre (rattan) available, Indonesiahas many raw material. From this case, this research conducted to get technical analysis of tensile strength andbending from rattan bark fibre composite that is using woven roving treatment of variation matting pattern onfibre direction 0º/90º and 45º angles as polyester resin matrix.The purpose of this research is: to identify the tensile strength and bending of composite of rattan bark fibrewhich influence fibre direction between 0º/90º and 45º angles. From the result of specimen trial is served intensile strength and bending, and compared with tensile strength and bending value which permitted by BKI (Biro Klasifikasi Indonesia) as theory of standardization trial. On the research, the writer found composite thathave rattan bark fibre compared 0º/90º and 45º angle of fibre direction, the treatment of matting pattern fibre,volume fraction 42,8% matrix polyester and 57,2% rattan bark fibre to specimen of tensile strength trial,volume fraction 50% matrix polyester and 50% rattan bark fibre to specimen bending trials. Conducted handlay up method, from the result study found the price maximum of tensile strength has got by composite with0º/90º and 45º fibre direction and maximum bending has got by composite with 45º fibre direction.